Study on the effect of Si-Ca-K-Mg fertilizer prepared from molybdenum tailings on the promotion of cherry radish production and the improvement of acidic soils - Hu, Tuanliu; Li, Yifan; Xiang, Aihua; Li, Xinglan; Liu, Kun (Penerbit Universiti Kebangsaan Malaysia, 2025)
Acidic soil extensively distributes in southern China, exerting an adverse influence on crop growth. The grade of molybdenum ore resources in China is relatively low, and a considerable amount of tailings are generated during the beneficiation process, which poses a significant threat to the environment. The application effect of converting molybdenum tailings into Si-Ca-K-Mg fertilizer on crops and acidic soils was studied. In this work, we used cherry radish and acidic soil in southern China as experimental materials, a 3-month pot experiment was conducted to study the application effect of Si-Ca-K-Mg fertilizer as a soil amendment on acidic soil and its growth promoting effect on cherry radish. Results indicated that the application of Si-Ca-K-Mg fertilizer significantly enhanced the growth indicators of cherry radish plants, encompassing length, weight, and chlorophyll content. The utilization efficiency of Ca, K, and Mg in the treatment group was significantly higher than the control group. Meanwhile, the application of the fertilizer facilitated the absorption of nitrogen (N) and phosphorus (P). Additionally, Si-Ca-K-Mg fertilizer can effectively improve key indicators in the soil, such as pH value, cation exchange capacity (CEC), available Si, K, Ca, and Mg. The experimental results demonstrated that the conversion of molybdenum tailings into Si-Ca-K-Mg fertilizer was a viable and effective approach.